2021
DOI: 10.3390/biom11050641
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of BDNF Genetic Variants and Smoking on Cognition in PTSD Veterans

Abstract: Posttraumatic stress disorder (PTSD) is frequently associated with cognitive disturbances and high prevalence of smoking. This study evaluated cognition in war veterans with PTSD and control subjects, controlled for the effect of smoking and brain derived neurotrophic factor (BDNF) rs6265 and rs56164415 genotypes/alleles. Study included 643 male war veterans with combat related PTSD and 120 healthy controls. Genotyping was done by real time PCR. Cognitive disturbances were evaluated using the Positive and Nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…The Val66Met polymorphism has been associated with PTSD diagnosis and symptom severity, although there are some inconsistencies between findings. Studies have found that the Met allele is overrepresented in PTSD populations compared to the Val/Val genotype [ 96 - 101 ]. The Met allele has also been associated with higher PTSD symptom severity than the Val/Val genotype [ 80 , 96 , 102 , 103 ].…”
Section: Val66met and Ptsdmentioning
confidence: 99%
“…The Val66Met polymorphism has been associated with PTSD diagnosis and symptom severity, although there are some inconsistencies between findings. Studies have found that the Met allele is overrepresented in PTSD populations compared to the Val/Val genotype [ 96 - 101 ]. The Met allele has also been associated with higher PTSD symptom severity than the Val/Val genotype [ 80 , 96 , 102 , 103 ].…”
Section: Val66met and Ptsdmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) and its associated receptor, tropomyosin receptor kinase B (TrkB), have come under increasing scrutiny for their role in several psychiatric disorders including PTSD ( 100 , 104 , 107 , 113 , 127 131 ). The synthesis of BDNF precursor pro-BDNF occurs in microglia, astrocytes, and glutaminergic neurons which is secreted along with the mature form of the neurotrophin, both of which are active ( 127 ).…”
Section: Mdmamentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) and its associated receptor, tropomyosin receptor kinase B (TrkB), have come under increasing scrutiny for their role in several psychiatric disorders including PTSD ( 100 , 104 , 107 , 113 , 127 131 ). The synthesis of BDNF precursor pro-BDNF occurs in microglia, astrocytes, and glutaminergic neurons which is secreted along with the mature form of the neurotrophin, both of which are active ( 127 ). BDNF signaling is associated with multiple aspects of neuroplasticity including the upregulation and phosphorylation of NMDARs and increases in the complexity, size, and number of dendritic spines at the synapse and is necessary for long-term potentiation and memory consolidation ( 132 , 133 ).…”
Section: Mdmamentioning
confidence: 99%
See 1 more Smart Citation